2024
DOI: 10.1093/ijnp/pyae020
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient Antipsychotic Use and Severe COVID-19: Avoiding the Impact of Age in a Real-World Data Study

Samuel Pintos-Rodríguez,
Irene Visos-Varela,
Almudena Rodríguez-Fernández
et al.

Abstract: Background The association between use of antipsychotics and COVID-19 outcomes is inconsistent, which may be linked to use of these drugs in age-related diseases. Furthermore, there is little evidence as regards their effect in the non-geriatric population . We aim to assess the association between antipsychotic use and risk of disease progression and hospitalisation due to COVID-19 among the general population, stratifying by age. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Chief among these was the inclusion of working-age patients with primary psychotic or mood disorders and older age patients suffering from dementia and medical comorbidities in single cohorts, despite their markedly different clinical profiles and underlying vulnerabilities to COVID-19 ( Boland and Dratcu, 2021 ). Pintos-Rodríguez et al (2024) have demonstrated that, when these shortcomings are addressed, evidence actually shows antipsychotics do not increase COVID-19–associated risks.…”
Section: Prescribing Antipsychotics and Covid-19: Databank Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Chief among these was the inclusion of working-age patients with primary psychotic or mood disorders and older age patients suffering from dementia and medical comorbidities in single cohorts, despite their markedly different clinical profiles and underlying vulnerabilities to COVID-19 ( Boland and Dratcu, 2021 ). Pintos-Rodríguez et al (2024) have demonstrated that, when these shortcomings are addressed, evidence actually shows antipsychotics do not increase COVID-19–associated risks.…”
Section: Prescribing Antipsychotics and Covid-19: Databank Researchmentioning
confidence: 99%
“…The controversy around the safety of antipsychotics during the COVID-19 pandemic illustrates how potentially misleading outcomes of some such studies may adversely affect clinical practice. Addressing this critical topic, the study by Pintos-Rodríguez et al (2024) raises highly pertinent questions regarding the credibility of large epidemiological studies that are entirely based on data obtained from secondary EMR databases but which fail to adopt adequate methodological safeguards.…”
mentioning
confidence: 99%